ОСОБЕННОСТИ ЭТИЧЕСКОГО ЖАНРА В АРАБСКОЙ ЛИТЕРАТУРЕ (Journal of Oriental Studies, 2016)
In the article the peculiarities of polite nesses genre arebeing determined and cleared up its place in the Arabicliterature. On the basing on valuable ideas of the orientalscientists are being informed about of polite nesses genre.